Diversity of anurans and use of microhabitats in three vegetation coverages of the Santuario de Flora y Fauna Los Colorados, Colombian Caribbean - Omer José Jiménez-Ortega; Keiner L. Tílvez; Joselin Castro-Palacios; Andrés García; Gabriel R. Navas; Julio Abad Ferrer-Sotelo; Dilia Naranjo-Calderón; Juan Gabriel Díaz-Castellar; Víctor Buelvas-Meléndez (Revista Mexicana de Biodiversidad)
This study aimed to determine anuran diversity and the use of microhabitats in 3 vegetation covers in the Santuario de Flora y Fauna Los Colorados. Five field trips of 6 days each were made, 2 days and 2 nights in each cover: forest, pasture, and crop. Sampling was carried out with the visual encounter inspection technique under a randomized design by random walks with manual capture. A total of 19 species were recorded, 14 in the forest, 13 in pasture, and 12 in crop. Pasture and crop were the vegetation covers with the greatest similarity of species. This work updates the list of anuran species recorded in the management plan of the Santuario de Flora y Fauna Los Colorados 2018-2023. The greatest number of anuran species was associated with leaf litter, "jagüeyes", and soils. The transformation of the landscape as a result of agriculture and cattle ranching generated changes in the richness, abundance, composition, and use of microhabitats of the anurans present in the Santuario de Flora y Fauna Los Colorados.